“Am I good enough?”: Progress uncertainty and the structural roots of self-doubt and wellbeing among Turkish doctoral students - Deniz, Berat (Journal of Interdisciplinary Studies in Education, 2026)
This phenomenological study examines how doctoral students in Turkish universities experience progress uncertainty, self-doubt, and wellbeing. Semi-structured interviews were conducted with 20 doctoral students across diverse disciplines and program stages. Findings reveal progress uncertainty as a distinct psychological stressor rooted in ambiguous expectations and invisible benchmarks. Progress uncertainty creates a reinforcing cycle with self-doubt, eroding wellbeing through chronic strain, work-life imbalance, and endurance-based coping. The Turkish context intensifies these dynamics through resource constraints, hierarchical supervision, and cultural expectations when institutions assume full-time student status despite employment realities. By demonstrating how progress uncertainty and self-doubt emerge from institutional structures rather than individual deficits, the study challenges individualistic approaches and points to structural interventions addressing institutional sources of uncertainty.